Wychowanie dziecka w rodzinie szlacheckiej w XVI i XVII wieku - Kahl, Edyta (Karkonoska Państwowa Szkoła Wyższa, 2011)
The issues of education and upbringing in nobility families in the context of XVI and XVII century society, culture, education models and family traditions are discussed in the article. Selected models of everyday activities and games as well as methods of influence as employed by the teachers and guardians to foster the physical, moral, intellectual and social development of children are examined. Roles of the father and the mother as well as other relatives and teachers are described. The discussion of practices is supplemented by an analysis of the views on family education as held by the scholars of pedagogy during Restoration. These opinions contain guidelines regarding e.g. proper hygiene and diet, morality and virtues as wellas the influence of the guardians on the child. By pinpointing various short comings of the process of education within nobility families the guidelines and suggestions provide for the enrichment of the picture of education and upbringing in those times.
Keywords: children; upbringing; care; family; nobility